Electric field driven phase transition and possible twining quasi-tetragonal phase in compressively strained BiFeO3 thin films - 陆成亮 刘俊明 吴韬 (Frontiers of physics, 2012)
Highly compressively strained BiFeO3 thin films with different thickness are epitaxially grown on （001） LaA103 substrates and characterized using various techniques. The quasi-tetragonal phase with a giant axial ratio of -1.25 and its thickness-dependent evolution are investigated. An inter- esting twining structure of the quasi-tetragonal phase is evidenced in thicker films through detailed reciprocal space mapping, which becomes more pronounced with increasing film thickness. More- over, an interesting electric-field driven phase transition was evidenced in the film with a thickness of 38 nm, in which the quasi-tetragonal and rhombohedral phases are close to each other in energy landscape.